1996
DOI: 10.1038/bjc.1996.81
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the monoclonal antibodies 17-1A and 323/A3: the influence of the affinity on tumour uptake and efficacy of radioimmunotherapy in human ovarian cancer xenografts

Abstract: Summary The low-affinity monoclonal antibody (MAb) chimeric 17-lA(c-17-lA) and the high-affinity MAb mouse 323/A3 (m-323/A3) were used to study the effect of the MAb affinity on the tumour uptake and efficacy of radioimmunotherapy in nude mice bearing subcutaneously the human ovarian cancer xenografts FMa, OVCAR-3 and Ov.Pe. Both MAbs are directed against the same pancarcinoma glycoprotein. In vitro, the number of binding sites on tumour cells at 40C was similar for both MAbs, but m-323/A3 had an approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Immunoperoxidase staining with 323/A3 showed that EGP40 was homogeneously distributed in each of the ovarian cancer xenografts and was highly expressed on the membrane. Autoradiography of the high-affinity MAb 323/A3 in FMa, OVCAR-3 and Ov.Sh xenografts indicated that 323/A3 was mostly located near blood vessels, while the low-affinity anti-EGP40 MAb 17-1A showed a homogeneous distribution pattern (Kievit et al, 1996). The preferential binding of high-affinity MAbs to tumor cells near blood vessels can likely be overcome by increasing the protein dose of the MAb (Blumenthal et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoperoxidase staining with 323/A3 showed that EGP40 was homogeneously distributed in each of the ovarian cancer xenografts and was highly expressed on the membrane. Autoradiography of the high-affinity MAb 323/A3 in FMa, OVCAR-3 and Ov.Sh xenografts indicated that 323/A3 was mostly located near blood vessels, while the low-affinity anti-EGP40 MAb 17-1A showed a homogeneous distribution pattern (Kievit et al, 1996). The preferential binding of high-affinity MAbs to tumor cells near blood vessels can likely be overcome by increasing the protein dose of the MAb (Blumenthal et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The MAbs 323/A3 and E48 were labeled with 125 I or 131 I (Amersham, 8s-Hertogenbosch, The Netherlands) with the use of iodogen (Kievit et al, 1996). More than 97% iodine was incorporated into the MAbs, as measured by TCA precipitation.…”
Section: Reagents Mabs and Iodinationmentioning
confidence: 99%
“…Similarly, in multiple subcutaneous tumor xenograft models, it was observed that a low affinity mAb was more homogenously distributed throughout the tumor than a mAb with a fivefold higher affinity. 21 While the range of affinities used in these studies was limited, or only compared a functional mAb to a nonspecific isotype matched control, the studies did demonstrate successfully that binding of antigen can limit penetration into a tumor.…”
Section: Experimental Analysis Of Affinity In the Binding Site Barriermentioning
confidence: 99%
“…17-1A is a chimeric mAb is directed towards a ~39 kDa membrane-associated pancarcinoma glycoprotein (Edwards et al, 1986;Koprowski et al, 1979). It has been used in one animal study (Kievit et al, 1996). 323/A3 is a murine mAb that is directed to a ~39 kDa membrane-associated pancarcinoma glycoprotein (same as 17-1A) (Edwards et al, 1986;Koprowski et al, 1979).…”
Section: Targeting Constructsmentioning
confidence: 99%
“…It emits -radiation (364 keV) enabling scintigraphy and dosimetry. 131 I has been used in animal studies (Kievit et al, 1996;Turner et al, 1998) and in clinical studies (Buchsbaum et al, 1999;Buijs et al, 1998;Buist et al, 1993;Colcher et al, 1987;Crippa et al, 1995;Epenetos et al, 1987;Mahé et al, 1999;Molthoff et al, , 1997Muto et al, 1992;Stewart et al, 1989aStewart et al, , 1989bVan Zanten-Przybysz et al, 2000. 186 and 188 .…”
mentioning
confidence: 99%